2015
DOI: 10.1073/pnas.1519644112
|View full text |Cite
|
Sign up to set email alerts
|

CREB pathway links PGE2 signaling with macrophage polarization

Abstract: Obesity is thought to promote insulin resistance in part via activation of the innate immune system. Increases in proinflammatory cytokine production by M1 macrophages inhibit insulin signaling in white adipose tissue. In contrast, M2 macrophages have been found to enhance insulin sensitivity in part by reducing adipose tissue inflammation. The paracrine hormone prostaglandin E2 (PGE2) enhances M2 polarization in part through activation of the cAMP pathway, although the underlying mechanism is unclear. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(198 citation statements)
references
References 27 publications
7
190
1
Order By: Relevance
“…These results are consistent with the widely accepted notion that PGE2 skews macrophages toward M2-type macrophages that promote tumor growth in the tumor microenvironment (32). The results also support the scenario that PGE2 release under hypoxic conditions in vivo is a newly identified mechanism of tumor immune evasion, wherein dying tumor cells assist the growth of surviving tumor cells by modifying the tumor microenvironment.…”
Section: Resultssupporting
confidence: 91%
“…These results are consistent with the widely accepted notion that PGE2 skews macrophages toward M2-type macrophages that promote tumor growth in the tumor microenvironment (32). The results also support the scenario that PGE2 release under hypoxic conditions in vivo is a newly identified mechanism of tumor immune evasion, wherein dying tumor cells assist the growth of surviving tumor cells by modifying the tumor microenvironment.…”
Section: Resultssupporting
confidence: 91%
“…6,20 Our previous work showed that CREB induces the M2 polarization of macrophages, an anti-inflammatory phenotype, via the induction of KLF4. 12 In the present work, we describe a previously unrecognized negative feedback mechanism for the regulation of NF-κB by TLR ligands via CREB-induced ICER. In this mechanism, ICER expression is upregulated by TLR ligands via p38-mediated CREB activation, and ICER, in turn, inhibits NF-κB transcriptional activity by interaction with the NF-κB p65 subunit.…”
Section: Discussionmentioning
confidence: 81%
“…We further evaluated the role of CREB in LPS-induced ICER expression by expressing the dominant-negative CREB inhibitor ACREB, a synthetic polypeptide that selectively heterodimerizes with, and disrupts, the DNA-binding activity of all CREB family members (CREB1, CREM, and ATF1) in WT PMs. 12 Similar to knocking out CREB in PMs, ACREB expression disrupted LPS-induced ICER gene expression (Figure 1g). Exposure to LPS consistently increased phospho-CREB occupancy over the ICER promoter in PMs (Figure 1h) and this effect was inhibited by SB203580 or SB202190 (Figure 1i).…”
Section: Figure 3 For Caption See Page 496mentioning
confidence: 86%
See 1 more Smart Citation
“…For mouse peritoneal Mfs, EpETrEs (particularly 11,12-EpETrE) regulated polarization by attenuating NF-kB via activation of peroxisome proliferator-activated receptor-a/g and heme oxygenase 1 (52). Via cAMP/cAMP response element binding protein, PGE 2 enhanced M2 polarization of mouse bone marrow-derived Mfs (53). PGE 2 also induced IL-10-producing Mfs in vitro and reduced allergic lung inflammation in mice (54).…”
Section: Discussionmentioning
confidence: 99%